Current Population Survey: Voter Supplement File, 1972 ([Verlag nicht ermittelbar], 1984)
This data collection supplies standard monthly labor force infomation for the week prior to the survey. Comprehensive information is given on the employment status, occupation and industry of persons 14 years old and older. Supplemental data on voter registration status, as well as detailed data on respondets' voting behavior in the November 7, 1972 general election is included. Information on demographic characteristics such as age, sex, race, martial status, veteran status, educational attainment, and household relationship, is available for each respondent.